Pengaruh Model Pembelajaran Role Playing terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas VIII SMP Negeri Bangunrejo - Wiji Rahayu; Isbandiyah Isbandiyah; Andriana Sofiarini (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effect of therole-playing learning model on student achievement insocial studies for eighth-grade students at Bangunrejo Public Junior High School. This study employs a quantitative approach using an experimental method. The research design used is a pretest-posttest control group design. The population in this study consists of all eighth-grade students at Bangunrejo State Junior High School for the 2025/2026 academic year, totaling 144 students. The research sample was determined using the Simple Random Sampling technique. The samples selected for this study were classes VIII.2 and VIII.3. Data collection was conducted through a test, with the research instrument consisting of a multiple-choice test comprising 35 questions. The data analysis technique used in this study wasquantitative analysis using a t-test. The results of this study showed that the pre-test score was 71%, and the hypothesis was tested, yielding t-calculated (0.414) < t-table most students scores were still below the criteria for achieving learning objectives. Meanwhile, the post-test score was 89%, and the hypothesis was tested, yielding t-calculated (-5.650) < t-table the students scores were above the criteria for achieving learning objectives. It can be concluded that the Role-Playing learning model has a significant effect on student learning outcomes in the Social Studies subject for 8th-grade students at Bangunrejo State Junior High School, falling into the “proficient” category.